From the individual to the collective: Repositioning assessment as a social practice - Cheng-Wen Huang; Shanali Govender; Daniela Gachago (University of Johannesburg, 2023)
Although assessment theorists have long argued that assessment is a contextually located social practice, objectivist and psychometric discourses about assessment persist. The COVID-19 pandemic, in many contexts, unsettled and denaturalised assessment practices, creating a critical disruptive moment. This paper presents a reflection on what this moment might suggest about academics' assessment beliefs and practices at a research-intensive institution in the Western Cape. Drawing on an institutional survey, we argue that dominant concerns about academic integrity and mark inflation surface discourses of assessment for certification and accountability. Exploring some examples of assessment practices during the emergency remote teaching period at the same institution, we highlight some factors that influence design. Drawing on Bourdieu's theory of practice, we contemplate the conditions of field and capital that create opportunities for change. We propose that change is contingent on the complex interplay of the capital and habitus of agents, as well as the nature of the field. We reaffirm the case for positioning assessment as a social practice, arguing that this enables the conditions for discussion, negotiation, and scrutiny on the purpose of assessments, what is being valued and not valued, and who is benefiting or being marginalised from particular assessment practices.